Transforming Mathematics Teaching Skills’ Pre-Service Teachers Using Digital Project Learning - Satriawati, Gusni; Darhim, Darhim; Asih, Endang Cahya Mulyaning; Martadiputra, Bambang Avip Priatna (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Technological Pedagogical Knowledge (TPK) is a skill that combines pedagogical and technological competencies to support teachers' professionalism in teaching mathematics in the era of digitalization. The purpose of this study is to determine the enhancement of TPK skills among Pre-Service Mathematics Teachers (PSMTs) who studied using a Digital Project Learning (DPL) approach compared to those who learned using a conventional approach. The research method used was an experiment with a posttest-only control group design. The research was conducted in the mathematics education study program at UIN Syarif Hidayatullah Jakarta during the 2023/2024 academic year, with the research sample comprising students from two classes enrolled in Mathematics Learning Strategy (MLS) courses. Seventy-two students enrolled in a mathematics learning strategies course were divided into an experimental group (n=34) and a control group (n=38). The instrument used in this study is a rubric-based observation sheet to assess students' TPK. The results showed that students in the experimental class had better TPK skills compared to PSMTs in the control class. This can be seen in the skills for designing learning and teaching, and in the diversity of technology use. Therefore, DPL is efficacious in improving the TPK skills of PSMTs.